1997
DOI: 10.2223/jped.550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of constipation in school children

Abstract: ResumoObjetivo: Obter a prevalência de constipação intestinal em escolares, tendo em vista que constipação crônica é freqüente em nosso ambulatório geral, mas são escassos os dados sobre prevalên-cia comunitária em crianças.Métodos: Foram avaliados 1145 alunos do ciclo básico (52,5% masculinos, idade mediana 8a 4m) de 5 escolas da periferia de Botucatu. As crianças responderam questionário previamente validado, aplicado por estudantes de Curso de Auxiliar de Enfermagem especialmente treinados. Exoneração de cí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
1
10
1
Order By: Relevance
“…This prevalence estimate is also higher than in most previous studies, where mean/median was reported to be 14 % respectively 12 %, but a wide range is reported depending on populations observed and criteria applied [4]. Other high estimates came from a study in Brasil with 28 % [8,10]. As in previous reports, there was no influence of socioeconomic data or gender on FC prevalence.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…This prevalence estimate is also higher than in most previous studies, where mean/median was reported to be 14 % respectively 12 %, but a wide range is reported depending on populations observed and criteria applied [4]. Other high estimates came from a study in Brasil with 28 % [8,10]. As in previous reports, there was no influence of socioeconomic data or gender on FC prevalence.…”
Section: Discussioncontrasting
confidence: 45%
“…Functional constipation (FC) and functional abdominal pain (FAP) are common problems in elementary school aged children with substantial impact on Quality of Life and usage of the Health Care System [1,2]. Relevant risk factors after exclusion of anorectal malformation or Hirschsprungs disease include nutritional factors (breastfeeding vs. formula, transition to solid foods, cow's milk protein allergy, low fibre and low liquids diet, fast food and lack of physical activity, obesity), environmental (socioeconomic status, family predisposition, urban living environment, parental rearing style), and behavioral factors (avoidance and retentive maneuvers, poor toilet training, history of violence in the family) [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Another study. 15 Reported higher prevalence amongst girls in school going children. The maximum prevalence was found in age group 4-6 yrs.…”
Section: Resultsmentioning
confidence: 99%
“…In a review of the literature, no consensus has been found regarding a specific gender predominance in pediatric constipation. 19 , 20 21 Obesity has been associated with poor response to therapy and has also been implicated as a risk factor for constipation. 22 But in the present study, only two participants were obese, not allowing this association to be further explored.…”
Section: Discussionmentioning
confidence: 99%